PROMOSI PERPUSTAKAAN OBJEK AMATAN: THE BRITISH COUNCIL LIBRARY JAKARTA - Fuady Munir (Jurnal IPI (Ikatan Pustakawan Indonesia), 2015)
This article is the result of BC (British Council) Library research as the object of its own research. The research was carried out by using library-research method, re-analyzing the existing quantitative data and conducting several interviews with informants to support the analysis. The study also evaluates the result of a survey which was conducted by a librarian on BC Library users in January 1996. The survey was conducted by applying accidental sampling (nonprobability sampling). From the survey, the data can be processed as many as 221 respondents. Meanwhile, qualitative data is obtained by performing in-depth question-and-answer sessions with the informants who were authorized by the respected agency. Therefore, the results of this research can not be generalized to other institutions.This library has made some improvements in terms oJ service, additional facilities, personnel qualities, as well as promotion. However, the number of the members who have been exposed by media campaigns such as billboards and the building is 7.69 percent and the advertisement is 4.52 percent. Thesefigures are very small compared to exposure through mouth-to-mouth campaign that achieves 57.01 percent. The question now is what kind of promotion that "fits" the BC?.